Pertumbuhan bibit tanaman karet dan perbandingan biaya pemupukan pada pengaplikasian pupuk daun dan pupuk akar - Putra, Riko Cahya; Susetyo, Imam (Politeknik Pertanian Negeri Pangkajene Kepulauan, 2025)
Fertilization can be applied through the leaves and roots, which have different characteristics and can complement each other. Foliar fertilizer suitable for use in rubber plant nurseries, other than Bayfolan, is Glow Green. This study aims to determine the growth of a rubber plant nursery using foliar fertilizer and root fertilizer, and to compare the fertilization costs. Research from April to September 2023 at the Bogor-Getas Unit Experimental Field, Salatiga. The experimental design used a randomized block design with 9 treatments and 3 replications. Treatments consisted of a control without fertilization, 50% root fertilizer, 100% root fertilizer, and a combination of root fertilizer at three dose levels (0%, 50%, 100%) with Bayfolan and Glow Green. Glow Green can reduce 50% dose of root fertilizer with plant height growth, stem diameter, and dry weight that are not significantly different compared to 100% root fertilizer and higher than 50% root fertilizer. The dry weight in the 50% root fertilizer + Bayfolan treatment was lower than in the 100% root fertilizer treatment. Treatment with 50% root fertilizer + Glow Green and 100% root fertilizer + Bayfolan showed higher relative agronomic effectiveness compared to 100% root fertilizer as the standard fertilization (RAE 108% and 105%), with fertilization costs of 89.8% and 117.5%. Glow Green is recommended for large-scale use in rubber nurseries, reducing fertilization costs by 10.2% and reducing the root fertilizer dose by 50%. At the same time, Bayfolan is applied without reducing the root fertilizer dose.